The Oxford Handbook of Christianity in Asia, edited by Felix Wilfred - Jones, Arun W. (Religions of South Asia, 2017)
The Oxford Handbook of Christianity in Asia, edited by Felix Wilfred. New York: Oxford University Press, 2014. xxi + 657 pp., 150.00 (hb). ISBN 978-0-19-932906-9 (hb).